Is There a Neuropathic-Like Component to Endometriosis-Associated Pain? Results From a Large Cohort Questionnaire Study - Coxon, Lydia; Wiech, Katja; Vincent, Katy (Frontiers in Pain Research, 2021)
Background: Pain is one of the primary symptoms of endometriosis, a chronic inflammatory condition characterised by the presence of endometrial tissue outside the uterus. Endometriosis-associated pain is commonly considered as nociceptive in nature, but its clinical presentation suggests that it might have neuropathic-like properties in a subgroup of patients. Methods: This is a cross sectional study using an online survey. The survey was distributed by patient support websites. The survey was composed of validated questionnaires assessing pain symptoms, psychological measures and questions about number of surgeries. Main Results: We had 1,417 responses which met the inclusion criteria. Using standard painDETECT cut-off scores, we found that pain was classified as neuropathic in 40% of patients and as mixed neuropathic/nociceptive in a further 35%. In line with observations in other neuropathic conditions, the neuropathic subgroup reported higher pain intensities, greater psychological distress and cognitive impairment. Neuropathic pain was also more likely in those with more surgeries to the abdomen and a longer history of pain. As revealed by a cluster analysis, those with a neuropathic pain component could further be divided into two subgroups based on their sensory profile. Conclusions: The data presented here indicate that endometriosis-associated pain includes a neuropathic-like component in a substantial proportion of women. Although further investigation is required, our finding challenges the current conceptualisation of endometriosis-associated pain as nociceptive and advocates for a new perspective on this type of pain, which is so debilitating to a large number of women.